Who Gets AIDS and How? The Determinants of HIV Infection and Sexual Behaviors in Burkina Faso, Cameroon, Ghana, Kenya and Tanzania - de Walque, Damien (World Bank, Washington, DC, 2012)
This paper analyzes the determinants of HIV infection and associated sexual behaviors using data from the first five Demographic and Health Surveys to include HIV testing for a representative sample of the adult population. Emerging from a wealth of country relevant results, four important findings can be generalized. First, married women who engage in extra-marital sex are less likely to use condoms than single women when doing so. Second, having been in successive marriages is a significant risk-factor, as evidenced by the results on HIV infection and on sexual behaviors. Contrary to prima facie evidence, education is not associated positively with HIV status. But schooling is one of the most consistent predictors of behavior and knowledge: education predicts protective behaviors like condom use, use of counseling and testing, discussion among spouses and knowledge, but it also predicts a higher level of infidelity and a lower level of abstinence. Finally, male circumcision and female genital mutilation are often associated with sexual behaviors, practices, and knowledge related to AIDS. This might explain why in the analysis in the five countries there is no significant negative association between male circumcision and HIV status, despite recent evidence from a randomized control trial that male circumcision has a protective effect.